Bovine lactoferrin suppresses inflammatory cytokine expression in endometrial stromal cells in chronic endometritis. (December 2022) - Nakamura, Akiko; Kimura, Fuminori; Tsuji, Shunichiro; Hanada, Tetsuro; Takebayashi, Akie; Takahashi, Akimasa; Kitazawa, Jun; Morimune, Aina; Amano, Tsukuru; Kushima, Ryoji; Murakami, Takashi
Abstract: Chronic endometritis (CE) is a type of chronic inflammation in the endometrium that is associated with infertility, which is primarily due to implantation failure. Antibiotics are the most common treatment for CE. However, some patients with CE are resistant to antibiotic treatment, while others refuse this treatment. Therefore, we focused on lactoferrin (Lf), which exhibits antimicrobial and anti-inflammatory properties, and studied its effect on inflammation in endometrial stromal cells (ESCs) from patients with CE. Endometrial tissue was collected from patients with CE, and ESCs were isolated and cultured. When ESCs were cultured with bovine lactoferrin (bLf: 1 mg/mL), the mRNA expression of TNF-α (p < 0.05) and IL-1β (p < 0.01) was significantly decreased compared with that in cells cultured without bLf. The level of TNF-α protein in the culture medium was significantly decreased (p < 0.01), while that of IL-1β was also decreased, but not significantly (p < 0.10), when 1 mg/mL of bLf was added to the culture medium. When more inflammation was induced artificially by adding 0.1 ng/mL of TNF-αto ESCs, the addition of bLf (1 mg/mL) to ESCs decreased IL-6 and IL-1β mRNA expression to levels similar to those in ESCs without TNF-α treatment. Furthermore, it was revealed that the actions of bLf are mediated by the AKT and MAPK intracellular signaling pathways, which are mechanisms by which the increase in TNF-α-induced cytokine expression is suppressed in ESCs. bLf suppresses the expression of inflammatory cytokines in human ESCs and may be a new therapeutic candidate for CE. Highlights: Lactoferrin suppresses the expression of inflammatory cytokines in endometrial stromal cells with chronic endometritis. Lactoferrin suppresses the inflammation that induced TNF-α in endometrial stromal cells. Akt and MAPK is involved in the anti-inflammatory effect of lactoferrin on endometrial stromal cells.